Influence of Post Mortem Muscle Activity on Turkey Meat Quality - Leishman, Emily M.; Vanderhout, Ryley J.; van Staaveren, Nienke; Barbut, Shai; Mohr, Jeff; Wood, Benjamin J.; Baes, Christine F. (Frontiers in Veterinary Science, 2022)
Wing flapping and body movement can occur during the slaughter of poultry. Wing movement and flapping are driven primarily by the breast muscles (Pectoralis major and minor), and this muscle activity may have implications for meat quality. The objective of this study was to evaluate turkey post mortem activity during slaughter at a commercial poultry processing plant. Post mortem activity (during bleeding) was scored on 5,441 male turkeys, from six different genetic lines, using a 1-4 scale from none to severe wing flapping. Meat quality was measured on these birds in terms of pH (initial, ultimate, delta or change), colour (L*, a*, b*), and physiochemical traits (drip loss, cooking loss, shear force). Linear mixed models were used to analyze the effect of activity (score 1-4), genetic line (A-F), and season (summer vs. autumn) on the nine meat quality traits. Post mortem activity influenced a*, drip loss, and shear force although the magnitude of the effects was small. There was an effect (P<0.05) of genetic line on all the meat quality traits except for L*, cooking loss, and shear force. In general, larger, faster-growing lines had higher pH, but the relationship between the lines for the other traits is not as clear. Season affected all the meat quality traits, except for pHdelta, with meat having a higher pH, L*, b*, drip loss, cooking loss and shear force in the summer. This study provides an exploratory assessment of post mortem activity in turkeys and identifies meat quality traits which are most affected while also accounting for the effects of genetic line and season. Although identified effect sizes are small, the cumulative effect on turkey meat quality may be more substantial.